Job choice and the influence of prior asthma and hay fever. Issue 7 (25th November 2010) - Butland, Barbara K; Ghosh, Rebecca; Strachan, David P; Cullinan, Paul; Jarvis, Deborah
Abstract : Objectives: To investigate whether prior symptoms of allergic disease influence first job undertaken on leaving school. Methods: The study included 5020 members of the 1958 British birth cohort who provided a job history (including start dates) at age 33 and for whom information on allergic disease in childhood and adolescence was reported by parents at ages 7, 11 and 16. Occupational group (high risk, low risk, reference) was based on first job and its probable asthma risk. Results: With occupational group defined using only job title, the RR of taking a high risk over a reference level job was an estimated 30% (RR ratio (RRR) 0.70; 95% CI 0.56 to 0.88) lower among those with than without prior reported symptoms of hay fever/allergic rhinitis but an estimated 60% (RRR 1.60; 1.17 to 2.19) higher among those with symptoms of asthma/wheezy bronchitis in adolescence compared to those with no history of asthma/wheezy bronchitis. With occupational group defined using an asthma specific job exposure matrix, a similar association was observed for prior hay fever/allergic rhinitis (RRR 0.77; 0.62 to 0.96) but not for asthma/wheezy bronchitis (RRR 1.18; 0.85 to 1.64). There was no evidence of an association between prior eczema and occupational group of first job. Conclusion: Whether our findings indicate avoidance or residual confounding, it would be prudent for future studies of occupation and the incidence or recurrence of asthma in adult life to adjust for any previous history of hay fever/allergic rhinitis.